2021
DOI: 10.1002/adem.202001047
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Research on the Oxidation Behavior of Refractory High Entropy Alloys

Abstract: Figure 4. Cross sections of various RHEA after oxidation in air (conditions in brackets): a) surface oxide layer (SOL) of the alloy TiZrNbHfTa(1 h at 700 C), [35] ODZ represents the oxygen diffusion zone. Reproduced with permission. [24] Copyright 2018, Wiley. b) Oxide scale formed on the alloy NbMoCrTiAl (100 h at 1000 C) [21] (mixed oxides consists of Nb 2 O 5 , TiO 2 , Cr 2 O 3 , Al 2 O 3 , and CrNbO 4 ). Reproduced with permission. [26] Copyright 2019, Elsevier. c) Backscattered electron (BSE) image of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(51 citation statements)
references
References 66 publications
(143 reference statements)
2
32
1
Order By: Relevance
“…A second prominent class of HEA systems are refractory high-entropy alloys (RHEAs), which comprise mostly refractory elements and invariably crystallize as body-centered cubic ( bcc ) solid solutions; these alloys have been considered as promising candidate materials for elevated-temperature applications due to their exceptional resistance to softening and extremely high melting points 9 11 . Although many practical challenges remain in the processing of RHEAs due to their brittleness and oxidation susceptibility 12 , numerous RHEAs have been designed, fabricated, and assessed experimentally, with additional insight coming from computational approaches 13 17 . Specifically, to investigate the deformation of RHEAs, transmission electron microscopy (TEM) studies on RHEAs have shown a dominant role of screw dislocations with increasing plastic strain 18 , 19 , and slip activity on high-order-planes has been observed through in situ scanning electron microscopy experiments 16 ; indeed, strong intrinsic lattice resistance has been generally found in these concentrated solid-solution alloys 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…A second prominent class of HEA systems are refractory high-entropy alloys (RHEAs), which comprise mostly refractory elements and invariably crystallize as body-centered cubic ( bcc ) solid solutions; these alloys have been considered as promising candidate materials for elevated-temperature applications due to their exceptional resistance to softening and extremely high melting points 9 11 . Although many practical challenges remain in the processing of RHEAs due to their brittleness and oxidation susceptibility 12 , numerous RHEAs have been designed, fabricated, and assessed experimentally, with additional insight coming from computational approaches 13 17 . Specifically, to investigate the deformation of RHEAs, transmission electron microscopy (TEM) studies on RHEAs have shown a dominant role of screw dislocations with increasing plastic strain 18 , 19 , and slip activity on high-order-planes has been observed through in situ scanning electron microscopy experiments 16 ; indeed, strong intrinsic lattice resistance has been generally found in these concentrated solid-solution alloys 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The oxidation performance of NV2 in the three pest oxidation temperatures was significantly better than that of the RHEAs or RCCAs, even those that were rich in Al content [ 4 , 52 ]. The contamination of the phases in the diffusion zone and in the bulk is compared in Figure 17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the addition of certain elements, such as Ti [ 154 ], Si [ 153 ], Cr [ 34 ] and Al [ 155 ], can significantly improve the oxidation resistance of RHEAs. During the oxidation process of W-containing RHEAs, complex oxidation products may be formed, having a significant impact on oxidation resistance [ 156 ]. How to improve the oxidation resistance is thus essential for the development and practical application of W-containing RHEAs.…”
Section: Functional Properties Of W-containing Rheasmentioning
confidence: 99%